2020
DOI: 10.1108/bfj-09-2019-0674
|View full text |Cite
|
Sign up to set email alerts
|

The influence of timing, location and social setting on hedonic and emotional evaluations of past eating experiences

Abstract: PurposeOur hedonic and emotional evaluations of the foods we encounter in daily life are predictive of whether we will choose to consume these foods in the future. Given the context-dependent nature of these evaluations and the rise in studies set in naturalistic and ecologically valid consumption settings, it is crucial that we examine the impact of contextual variables on our current consumer emotion measurement methods.Design/methodology/approachThree important factors that influence meal-evoked emotion – m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…As discussed in Introduction, such inconsistencies likely stem from the tendency in most emotional eating studies to predominantly focus on negative emotions, an approach based on the widespread assumption that, given individuals’ inherent desire to avoid harm, negative emotions automatically induce eating ( Macht, 1999 ). Recent studies (e.g., Altheimer and Urry, 2019 ; Nath et al, 2020 ), however, have suggested that individuals’ emotional eating might be a behavioral tendency learned from their cumulative socialization process rather than being an inherent characteristic. These studies have further gone on to suggest that some positive emotions could ironically induce food craving and emotional eating behavior (e.g., hedonic and happy eating phenomena; Bongers et al, 2013 ; Salerno et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As discussed in Introduction, such inconsistencies likely stem from the tendency in most emotional eating studies to predominantly focus on negative emotions, an approach based on the widespread assumption that, given individuals’ inherent desire to avoid harm, negative emotions automatically induce eating ( Macht, 1999 ). Recent studies (e.g., Altheimer and Urry, 2019 ; Nath et al, 2020 ), however, have suggested that individuals’ emotional eating might be a behavioral tendency learned from their cumulative socialization process rather than being an inherent characteristic. These studies have further gone on to suggest that some positive emotions could ironically induce food craving and emotional eating behavior (e.g., hedonic and happy eating phenomena; Bongers et al, 2013 ; Salerno et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, research suggests that individuals who have previous associations between emotions and eating are likely to show chronic tendencies of emotional eating ( Altheimer and Urry, 2019 ), resulting in health risks such as severe obesity, diabetes, and heart disease ( Nath et al, 2020 ). Media managers and legislators should then pay a closer attention to emotionally positioned advertising campaigns given that among the four types of discrete emotions examined, anger (experienced through close and decisive losses) has the greatest potential to evoke emotional eating.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation